Insulin and GLP‐1 infusions demonstrate the onset of adipose‐specific insulin resistance in a large fasting mammal: potential glucogenic role for GLP‐1. Issue 2 (8th July 2013) - Viscarra, Jose A.; Rodriguez, Ruben; Vazquez‐Medina, Jose Pablo; Lee, Andrew; Tift, Michael S.; Tavoni, Stephen K.; Crocker, Daniel E.; Ortiz, Rudy M.
Abstract Prolonged food deprivation increases lipid oxidation and utilization, which may contribute to the onset of the insulin resistance associated with fasting. Because insulin resistance promotes the preservation of glucose and oxidation of fat, it has been suggested to be an adaptive response to food deprivation. However, fasting mammals exhibit hypoinsulinemia, suggesting that the insulin resistance‐like conditions they experience may actually result from reduced pancreatic sensitivity to glucose/capacity to secrete insulin. To determine whether fasting results in insulin resistance or in pancreatic dysfunction, we infused early‐ and late‐fasted seals (naturally adapted to prolonged fasting) with insulin (0.065 U/kg), and a separate group of late‐fasted seals with low (10 pmol/L per kg) or high (100 pmol/L per kg) dosages of glucagon‐like peptide‐1 (GLP‐1) immediately following a glucose bolus (0.5 g/kg), and measured the systemic and cellular responses. Because GLP‐1 facilitates glucose‐stimulated insulin secretion, these infusions provide a method to assess pancreatic insulin‐secreting capacity. Insulin infusions increased the phosphorylation of insulin receptor and Akt in adipose and muscle of early‐ and late‐fasted seals; however, the timing of the signaling response was blunted in adipose of late‐fasted seals. Despite the dose‐dependent increases in insulin and increased glucose clearance (high dose), both GLP‐1 dosages produced increases in plasma cortisol and glucagon, which may have contributed to the glucogenic role of GLP‐1. Results suggest that fasting induces adipose‐specific insulin resistance in elephant seal pups, while maintaining skeletal muscle insulin sensitivity, and therefore suggests that the onset of insulin resistance in fasting mammals is an evolved response to cope with prolonged food deprivation.